104k views
2 votes
Simplify.

Rewrite the expression in the form 4^x.

4^4 x 4^3 = ??

User Alex Baker
by
5.2k points

1 Answer

4 votes

Answer:


4^(7)

Explanation:

To simplify the expression
4^(4)*4^(3), we can use the first law of the law of indices which states that the exponent is added together when multiplying numbers with the same base. Eg:
a^(x)* a^(y) = a^(x+y).


4^4 *4^3=4^(4+3)


=4^(7)

Hope this helps :)

User Gabrtv
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.